2019
DOI: 10.7150/thno.31037
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine-type cathepsins promote the effector phase of acute cutaneous delayed-type hypersensitivity reactions

Abstract: Cysteine-type cathepsins such as cathepsin B are involved in various steps of inflammatory processes such as antigen processing and angiogenesis. Here, we uncovered the role of cysteine-type cathepsins in the effector phase of T cell-driven cutaneous delayed-type hypersensitivity reactions (DTHR) and the implication of this role on therapeutic cathepsin B-specific inhibition. Methods : Wild-type, cathepsin B-deficient (Ctsb -/- ) and cathepsin Z-deficient (Ctsz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Psoriasis is an immune-mediated chronic skin disease, which is prone to relapse and affects approximately 2% of the population worldwide 1 . Although the pathogenesis of psoriasis remains unclear, it has been widely recognized that T cells, especially CD4 + Th17 and IL-17-producing γδ T cells, play an important role in the development and progression of psoriasis 2 , 3 and cutaneous DTH responses 4 . The accumulation of Th17 cells in the dermis can lead to the aberrant differentiation and proliferation of keratinocytes by producing abundant proinflammatory cytokines, such as IL-6, IL-17A and IL-22 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is an immune-mediated chronic skin disease, which is prone to relapse and affects approximately 2% of the population worldwide 1 . Although the pathogenesis of psoriasis remains unclear, it has been widely recognized that T cells, especially CD4 + Th17 and IL-17-producing γδ T cells, play an important role in the development and progression of psoriasis 2 , 3 and cutaneous DTH responses 4 . The accumulation of Th17 cells in the dermis can lead to the aberrant differentiation and proliferation of keratinocytes by producing abundant proinflammatory cytokines, such as IL-6, IL-17A and IL-22 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The multifactorial pathogenesis contributing to the psoriasis phenotype involves genetic, environmental and immunological factors 2 . Psoriasis is generally manifested as chronic inflammation of the skin and is characterized by circumscribed, scaling, and erythaematous plaques 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors also showed a redundancy in cathepsin function, with cathepsin Z, a protease closely related to cathepsin B, showing a compensatory expression in inflamed ears of cathepsin B-deficient (Ctsb −/− ) mice. In turn, cathepsin B expression was equally elevated in cathepsin Z-deficient (Ctsz −/− ) mice [ 89 ]. Interestingly, the functional redundancy of cathepsins was also reported by Orlowski and colleagues, which demonstrated that although being involved in IL-1β secretion, cathepsins also regulate pro-IL-1β synthesis [ 90 ].…”
Section: Skin Sensitizers and Danger Signalsmentioning
confidence: 99%